RENAISSANCE REDEFINED: INFLUENCE AND EFFECT OF RENAISSANCE PARLANCE ON WESTERN CULTURAL AND GEOGRAPHICAL AMBIENCE. - Nair, Jithesh J.; Panicker, Joji John (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Renaissance, a pivotal cultural movement from the 14th to the 17th centuries, profoundly shaped Western cultural ambiance through its influence on art, architecture, music, and literature. This abstract explores the transformative effects of Renaissance parlance on these domains, emphasizing its role in the evolution of Western aesthetics and intellectual thought. Renaissance parlance encouraged a return to classical ideals in art, emphasizing realism, proportion, and perspective, thereby revolutionizing visual representation. Architectural advancements during this period, marked by a revival of Greco-Roman elements and innovative structural techniques, epitomized the Renaissance’s commitment to symmetry and harmony. In music, the era’s linguistic and cultural shifts facilitated the development of polyphonic textures and expressive forms, reflecting a deepened appreciation for human emotion and narrative. Literary contributions of the Renaissance, characterized by a renewed focus on humanism and classical themes, significantly influenced narrative structure and poetic form. This examination underscores how Renaissance parlance, with its emphasis on classical revival and humanistic inquiry, left an indelible mark on Western cultural expressions, fostering a legacy of aesthetic and intellectual advancements that continue to resonate in contemporary Western culture.